Identification and characterization of multiple novel viruses in fecal samples of cormorants - Ji, Li; Zhao, Ran; Pei, Yifei; Sun, Yijie; Sun, Xiaoyi; Ji, Likai; Wang, Xiaochun; Liu, Yuwei; Shen, Quan; Yang, Shixing; Wang, Yan; Zhang, Wen (Frontiers in Veterinary Science, 2025)
IntroductionCormorants, as protected wild animals by the State Forestry Administration of China, have a broad distribution across China. Previous studies have shown that they can be infected with multiple viruses in the Flaviviridae, Orthomyxoviridae, Paramyxoviridae, and Polyomaviridae families. There is limited knowledge about the other viruses that cormorants may carry and infect.MethodsIn this study, we employed viral metagenomics to identify novel viruses in the fecal samples collected from cormorants in Xiamen City, Fujian Province, China.ResultsTwo novel viruses were identified, including one novel picornavirus named Cormhepa01 and one novel avain hepevirus named CormhepaE. The genome of Cormhepa01 is 7,463 bp in length, which encodes a 2,260 aa polyprotien. Similar to other known picornaviruses, the conserved NTPase, proteinase, and polymerase motifs are presented in the 2C, 3C, and 3D proteins separately. Based on the phylogenetic analysis and amino acid sequence alignment, the CormhepaE may be assigned to a new picornavirus genus. The partial genome of CormhepaE is 6,546 bp in length. Compared with other avian hepatitis E virus strains, CormhepaE has multiple variable sites, which are distributed in motifs of the methyltransferase, helicase, and RdRp domains, separately. Based on the phylogenetic analysis, CormhepaE, together with another strain MG737712 isolated from sparrow, formed a new species of the Avihepevirus genus in the Hepeviridae family.ConclusionWe identified and characterized two novel cormorant viruses in this study. The findings of this study increase our understanding of the diversity of viruses in cormorants and provide practical viral genome information for the prevention and treatment of potential viral diseases affecting this species.